Functionalized Oxoindolin Hydrazine Carbothioamide Derivatives as Highly Potent Inhibitors of Nucleoside Triphosphate Diphosphohydrolases - Afzal, Saira; al-Rashida, Mariya; Hameed, Abdul; Pelletier, Julie; Sévigny, Jean; Iqbal, Jamshed (Frontiers in Pharmacology, 2020)
Hydrazine carbothioamide derivatives were identified as potent and selective nucleoside triphosphate diphosphohydrolase-3 (NTPDase3) modulators. We conducted a study to synthesize and characterize a series of oxoindolin hydrazine carbothioamide derivatives using spectroscopic techniques including IR, 1H-NMR, 13C-NMR and ESI-MS. The developed derivatives were further investigated for their modulatory effects on ectonucleotidase activity in vitro. Of screened derivatives, two lead candidates, 8c (IC50 = 0.19 ± 0.02 µM) and 8m (IC50 = 0.38 ± 0.03µM) showed submicromolar potencies as h-NTPDase3 inhibitors. Furthermore, their effect on glucose stimulated insulin secretion was demonstrated with mice Langerhans islets. However, while compound 8m affected insulin secretion, 8c did not. Compound 8m also showed inhibition of NTPDase3 in islet cells but showed no pronounce effect on NTPDase3 gene expression suggesting its direct effect to regulate insulin secretion. Collectively, these findings underline the potential of hydrazine carbothioamide derivatives as novel h-NTPDase3 inhibitors thereby providing insights for the development of new antidiabetic drugs.